ODONTECTOMY MANAGEMENT WITH LOCAL ANESTHESIA IN PATIENT WITH OPEN-ANGLE GLAUCOMA - Bramasto Purbo Sejati; Bambang Dwiraharjo; Elizabeth Riyati Titi Astuti (FKG Unlam, 2021)
Background: Glaucoma is characterized by optic neuropathy with increased intraocular pressure. The high prevalence of impaction causes some glaucoma patients to require odontectomy. There are no contraindications to odontectomy in glaucoma patients, but special preparation is needed to prevent recurrence during the procedure. Glaucoma recurrence is precipitated by increased intraocular pressure which correlates with elevated systemic blood pressure with increased intraocular pressure and corticosteroid use. Therefore, dentists must be vigilant in choosing an atraumatic odontectomy procedure, anesthetic dose and techniques, as well as administering the type and dose of analgesics. Objective: This paper reports a case of mandibular third molar odontectomy with local anesthesia in a patient with open-angle glaucoma, which is a rare case and in this case there is a high risk of complications. Case: A 26-year-old male patient complained of pain in the left back gum when chewing. Orthopantomographic radiographic examination showed impacted 38. The patient has been diagnosed with open-angle glaucoma for 5 years. An odontectomy was performed under local anesthesia. Durante surgery, bleeding is minimal and does not cause recurrence of glaucoma. Postoperative evaluation gave good results, minimal complications, and no recurrence of glaucoma.Conclusion: Odontontectomy with local anesthesia in glaucoma patients requires special preparation in the form of atraumatic surgical procedures and perioperative pharmacotherapy management in the form of pre-emptive analgesia, selection of a maximum of two ampoules of lidocaine and epinephrine 1:80,000 with the mandibular block anesthetic technique, and using multimodal analgesia in combination with NSAIDs without corticosteroids. Keywords: Complications, Glaucoma, Odontectomy